The Prostitute as a commentary of the State in postcolonial Africa: The case of Okey Ndibe’s Arrows of rain - Barasa, Violet N. (African Journal of Education,Science and Technology (AJEST), 2021)
The essay examines Okey Ndibe’s Arrows of rain to probe how he uses the figure of the prostitute to engage and interrogate political leadership and governance in fictional Madia. The paper argues that the prostitute by nature of her work and position, is marginalized in that she subverts societal moral order. However, I point out that the position of the prostitute in Arrows of rain serves as an appropriate vantage point from which the author explores a number of maladies afflicting contemporary African states. Of significance in the essay is the personality of Emilia’s name duality as a prostitute and a profession teacher. Therefore, by interrogating the figure of the prostitute, the paper posits that the prostitute through her actions, speech and silences has been used as a strategy of representing the failed promises of the state in postcolonial Madia and Africa in general. In the main, the paper focuses on the intricacies around political leadership and the missteps of the leader are interrogated through his association with the prostitute. It is therefore within such a relationship that embeds failures of the leader. The question that arises from such a relationship between a prostitute and a leader is who of the two is “immoral”? Is there a possibility of reading political leadership in Africa against moral inadequacy as it is the case of a prostitute? The responses to the raised questions forms the basis of the analysis in this paper as I seek to demonstrate how the prostitute has been used deliberately to expose the social ills perpetrated by the leader.